The structuring levers of the competitiveness of the Algerian economy Lessons from a benchmark with some comparable economies: Morocco, Tunisia, Turkey, South Korea, Malaysia - Karim MAHOUI; Nabil BOUDA; Nasreddine BENNACER (Journal of North African Economies, 2025)
This contribution aims to identify the levers, if they are implemented, that would allow Algeria's economy to be competitive and to begin to overcome its structural dependence on hydrocarbons. After highlighting the differences in the definition of competitiveness and choosing the structural dimension to evaluate the state of the Algerian economy, a benchmark approach was undertaken with a few comparable economies (Tunisia, Morocco, Turkey, South Korea, and Malaysia) to measure the distance in performance that separates the national economy from these economies, based on four structuring levers (a voluntarist policy, controlled international openness, targeted support for SMEs and an education system that is equal to the economic challenges). The results of the benchmark confirm that competitiveness in its structural dimension is the result of a policy that is built over the long term and that the underperformance recorded by Algeria requires urgent action and structural reforms.